(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides an overview of the International Phonetic Alphabet (IPA) and its applications to English. It begins by explaining the purpose and structure of the IPA, emphasizing its role as a universal system for transcribing speech sounds across languages. The article highlights how the IPA addresses the complexities of English, particularly its irregular spelling and diverse accents, by offering a consistent method for representing pronunciation.